台灣學生網路相關著作權、學術寫作倫理課程之發展與評量研究 - 周倩; CHOU CHIEN (My University, 2011)
台灣學生網路相關著作權、學術寫作倫理課程之發展與評量研究 中文摘要 本研究群擬提出三年期計畫，分為二個面向進行。第一個面向是超越著作權的範疇，針 對學術寫作倫理—不抄襲、不剽竊，為各級學生—從小學高年級到大學—具體設計與發展有 關網路著作權、學術寫作倫理的課程，並進行教學實驗，透過教育管道教導學生正確的網路 相關著作權、學術寫作倫理、改寫與引用方式。課程的設計將築基於傳播學理論「慎思可能 性模式」（Elaboration Likelihood Model, ELM），並採用「案例教學法」、「概念卡通」，以及「雙 層次測驗」來進行。本研究之第二個重要面向，將特別針對學生網路著作權概念與英文寫作 剽竊之觀念、態度、行為等面向，進行深度探討，藉以釐清學生英文寫作剽竊的行為（特別 是文句抄襲的現象）與其對於著作權之觀念與行為間，是否有相互關聯性。另外，本計畫也 試著把學生將網路資源成為寫作剽竊的「抄襲資源」，轉化為寫作的「學習資源」。透過網路 引導學生如何找尋語言的參考資訊，並透過改寫（paraphrasing）過程，轉化為自己的文字， 並進而增強學生的英文寫作能力。

The Development and Evaluation of Curricula on Cyber Copyright and AcademicWriting Ethics for Taiwan Students Abstract This three-year project has two major facets. The first one is the introduction of cyber copyright and ethics of academic writing (not-plagiarism) to Taiwan students from elementary school through college levels. This project will design and develop the curricula on the cyber copyright concepts, academic writing, and ethics. The underlying theory to guide the instructional design is the Elaboration Likelihood Model, and the teaching strategies incorporate case-based instruction, concept cartoon, and two-tier tests. The second facet will focus on the relationship between college students’English writing plagiarism behaviors and their understanding of cyber copyright. Further, this study will explore how to change students’plagiarism resource—the Web—to their learning resource. By Web-based guidance, students will be able to search for writing references and process through paraphrasing to improve their academic writing performance.
The Development and Evaluation of Curricula on Cyber Copyright and Academic Writing Ethics for Taiwan Students
Keywords: 剽竊; 抄襲; 讀寫; Plagiarism; paraphrasing; readability; L2 writing; read-to-write